Sistema de aeração para silos de armazenagem de grãos com a utilização de termometria digital - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Brazil has a very large deficit in static grain storage capacity compared to what is produced and, as a result of this statement, it is expected that more and more new grain storage units will be built. The installation of thermometry systems in storage units is mandatory for them to be accredited, so the market will have to supply this demand. The thermometry systems installed in most units are thermocouple sensors and there is a great possibility that this system can be replaced by systems with digital sensors. The present work presents the development of a thermometry system that uses digital sensors and allows the visualization and interaction of the user with the project variables, including activating the aeration system remotely. As results will be presented the operation and the advantages identified in the proposed system in relation to the systems that use thermocouples.
Keywords: Engenharia elétrica; Termometria; Aeração; Sensores digitais; Electrical engineering; Thermometry; Aeration; Digital sensors; CNPQ::ENGENHARIAS